ANALISIS POTENSI PENGEMBANGAN TANAMAN PANGAN BERBASIS KOMODITAS LOKAL DI KECAMATAN KALEDUPA KABUPATEN WAKATOBI - Arif, La Ode Kasno; Jayadisastra, Yoenita; Abadi, Musram; Iswandi, R Marsuki; Alwi, La Ode; Sudarmo, Hadi; Dedu, La Ode Arfan (Fakultas Pertanian Universitas Halu Oleo, 2023)
The aims of this study was to identify the potential distribution of land for developing food crops, and to analyze the types of local food crops that have the potential to be developed in Kaledupa District. The research data is primary data through direct observation and interviews with stakeholders, namely agricultural service officials, coconut villages, farmers, heads of farmer groups, and researchers. Data analysis is a descriptive approach and GIS (Geographic Information System) analysis to describe land potential, and the Analytical Hierarchy Process to determine priority food crops. The results of the analysis of the potential land for food crops are known to be spread over 12 village areas with a total potential land area of 957.68 ha. The dominant existing food crops are found in seven village areas namely Ollo, Balasuna, Balasuna Selatan, Laulua, Horuo, Kalimas and Sombano. The priority criterion for developing food crops is market demand with a weight value of 0.409, while the priority scale for food crops is cassava with a weight value of 0.352. The development of food crop agriculture should be adapted to the potential of land resources and local commodities, thereby helping efforts to increase production and farmer welfare